2019
DOI: 10.1088/1361-6560/aaf5e9
|View full text |Cite
|
Sign up to set email alerts
|

Robust optimization to reduce the impact of biological effect variation from physical uncertainties in intensity-modulated proton therapy

Abstract: 12Purpose: Robust optimization (RO) methods are applied to intensity-modulated proton therapy (IMPT) 13 treatment plans to ensure their robustness in the face of treatment delivery uncertainties, such as 14 proton range and patient setup errors. However, the impact of those uncertainties on the biological 15 effect of protons has not been specifically considered. In this study, we added biological effect-based 16 objectives into a conventional RO cost function for IMPT optimization to minimize the variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…3), which indicates that the biological dose derived by the TPS is closer to the “true” biological dose, and thus is more reliable in robust plans than in PTV‐based plans. A similar trend was observed in the biological surrogate according to the study conducted by X. Bai et al With this, the authors carried out further analysis of the correlation between the difference of ΔDtruemax among the optimization techniques and the CTV‐to‐OAR distance, which showed a large value when the OAR was closer to the CTV.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…3), which indicates that the biological dose derived by the TPS is closer to the “true” biological dose, and thus is more reliable in robust plans than in PTV‐based plans. A similar trend was observed in the biological surrogate according to the study conducted by X. Bai et al With this, the authors carried out further analysis of the correlation between the difference of ΔDtruemax among the optimization techniques and the CTV‐to‐OAR distance, which showed a large value when the OAR was closer to the CTV.…”
Section: Discussionsupporting
confidence: 73%
“…Thus far, a good number of research works have conducted a comparative study of biological surrogate and LET distributions among different optimization techniques. If the optimization techniques are confined to only those available in commercial TPS, then the recent study by X. Bai et al shows that robust optimization can reduce both the biological surrogate and the LET at OARs, causing less biological damage to the OARs than PTV‐based plans because the former tends to use lateral fall‐off to spare the OARs rather than the distal edge . D. Giantsoudi et al demonstrated a series of Pareto‐optimal IMPT base plans showing substantial LET variations, which leads to potentially considerable differences in RBE‐weighted doses in terms of multicriteria optimization .…”
Section: Introductionmentioning
confidence: 99%
“…35 LET d distributions differ between those two treatment planning approaches. 20 However, the optimization strategy in this study, using either SFO or MFO, had neither a relevant impact on absolute LET d values in OARs and CTVs nor on their sensitivity to range uncertainties when applying robust dose optimization. LET d distributions in the target volumes of all entities were rather homogeneous, comparable in LET d magnitude, and essentially insensitive against the uncertainty in range prediction.…”
Section: Discussionmentioning
confidence: 70%
“…This includes the use of robust dose optimization, 19 which results in LET d distributions differing from those based on the traditional concept using a planning target volume. 20 Furthermore, a comprehensive LET d quantification with uncertainty estimates for relevant patient cases is vital before explicitly including the LET d in future clinical proton treatment planning. Biological dose distributions in organs at risk (OARs) estimated by RBE models based on in vitro data need to be complemented with clinically derived models for normal tissue complication probability (NTCP) and their uncertainties to facilitate the translation of improved biological dose concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Inaniwa et al 19 minimized the physical dose and LET d based on prescribed values in a quadratic cost function, while Cao et al 20 added two terms for maximizing LET-weighted dose in the target and minimizing it in OARs without considering any prescription. To deal with plan robustness under proton range and patient setup uncertainties, An et al 21 minimized the highest LET in OARs while maintaining the same dose coverage and robustness in tumor targets as the conventional robust IMPT treatment plan model, while Bai et al 22 penalized the sum of the differences between the highest and lowest biological effect in each voxel, approximated by the product of dose and LET, to achieve robust biological effect and physical dose distributions in both target and critical structures. However, these approaches typically used optimization priorities to control the trade-off dynamic between dose and LET criteria.…”
Section: Introductionmentioning
confidence: 99%